2012
DOI: 10.5116/ijme.4f7e.e332
|View full text |Cite
|
Sign up to set email alerts
|

Improving empathy of physicians through guided reflective writing

Abstract: Objectives: This study was designed to explore how guided reflective writing could evoke empathy and reflection in a group of practicing physicians. Methods: Total participants recruited included 40 staff physicians at Cleveland Clinic, a tertiary care academic medical center. Twenty physicians (intervention group) were assigned to participate in a 6-session faculty development program introducing narrative medicine and engaging in guided reflective writing. Ten physicians (comparison group 1) received the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
0
31
0
8
Order By: Relevance
“…Each study was appraised using tools and guidance designed by the evidence for policy and practice information and coordinating centre14 and the critical appraisal skills programme 15Studies appraised by this review Quantitative study Tsai and Ho16 Combined quantitative and qualitative studies Shapiro et al 19 Misra-Hebert et al 20 Lancaster et al 22 Qualitative studies Clandinin and Cave24 Lazarus and Rosslyn28 Arntfield et al 26 Gull et al 29 DasGupta and Charon27 …”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Each study was appraised using tools and guidance designed by the evidence for policy and practice information and coordinating centre14 and the critical appraisal skills programme 15Studies appraised by this review Quantitative study Tsai and Ho16 Combined quantitative and qualitative studies Shapiro et al 19 Misra-Hebert et al 20 Lancaster et al 22 Qualitative studies Clandinin and Cave24 Lazarus and Rosslyn28 Arntfield et al 26 Gull et al 29 DasGupta and Charon27 …”
Section: Methodology and Methodsmentioning
confidence: 99%
“…However, Cataldo and colleagues (2005) found no significant increase in the JSE scores as a result of Balint training among residents in a family medicine residency program. In a qualitative and quantitative study with 40 staff physicians at the Personality assessments in medical education Cleveland Clinic, it was found that a faculty development program using guided narrative writing could influence, to a limited extent, the empathy of practicing physicians (Misra-Herbert et al 2012).…”
Section: Enhancement Of Empathy In Medical Educationmentioning
confidence: 99%
“…Reliable tools have been validated and published, including physician-patient relationship assessment questionnaires [19] and communication observation grids [20]. Physicians can use these tools for self-evaluation and patients for assessing the quality of their relationship with their physician [21]. However, the array of tools for assessing the quality of the therapeutic relationship remains limited, and further research is needed in this field.…”
Section: Therapeutic Patient Education (Tpe) Requires Training In Nonmentioning
confidence: 99%